2021
DOI: 10.1063/5.0055779
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent dynamic structure factors for liquid water inferred from inelastic neutron scattering measurements

Abstract: Temperature-dependent dynamic structure factors S(Q, ω) for liquid water have been calculated using a composite model, which is based on the decoupling approximation of the mean square displacement of the water molecules into diffusion and solid-like vibrational parts. The solid-like vibrational part S vib (Q, ω) is calculated with the phonon expansion method established in the framework of the incoherent Gaussian approximation. The diffusion part S diff (Q, ω) relies on the Egelstaff-Schofield translational d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Experimentally, jump models have been used to analyze water QENS spectra, 9,10,[28][29][30][31] and translational jump time values close to the values obtained here have been shown to be consistent with experimental linewidths. 30 However, QENS spectra probe displacements of water H atoms 28 and, while the latter share the same diffusion coefficient as water O atoms, their motions result from the combination of larger-amplitude jumps when the H atom exchanges H-bond acceptors and smaller-amplitude jumps when the parent O atom experiences an H-bond exchange which does not involve this H. A specific translational jump model for water H atoms combining these two types of exchanges would thus provide a way to model QENS spectra without having to use the traditional but questionable translationrotation decoupling approximation.…”
supporting
confidence: 80%
“…Experimentally, jump models have been used to analyze water QENS spectra, 9,10,[28][29][30][31] and translational jump time values close to the values obtained here have been shown to be consistent with experimental linewidths. 30 However, QENS spectra probe displacements of water H atoms 28 and, while the latter share the same diffusion coefficient as water O atoms, their motions result from the combination of larger-amplitude jumps when the H atom exchanges H-bond acceptors and smaller-amplitude jumps when the parent O atom experiences an H-bond exchange which does not involve this H. A specific translational jump model for water H atoms combining these two types of exchanges would thus provide a way to model QENS spectra without having to use the traditional but questionable translationrotation decoupling approximation.…”
supporting
confidence: 80%
“…There have been several efforts to study the effects of temperature on the structure and dynamics of pure and isotopically diluted water. , These studies have shown that the hydrogen bonds become weaker and break more frequently on increase of temperature. Both the infrared and Raman spectra of the OH stretch shift toward the blue side on increase of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…for liquid water at ambient conditions and inelastic neutron scattering at various temperatures [43]. MD results of the coherent dynamic structure factor of liquid water at the mesoscale have been presented by Alvarez et al [44].…”
Section: Dynamical Correlations Have Lately Been Reported From Inelas...mentioning
confidence: 95%